The Effect of Work-Family Conflict and Job Stress on the Performance of Female Inpatient Nurses with Motivation as an Intervening Variable at Petala Bumi Regional General Hospital Pekanbaru City - Fadli Fatihul Ichsan; Dewita Suryati Ningsih; Dian Puspita Novrianti (West Science Business and Management, 2026)
Petala Bumi Regional General Hospital is a Type C hospital located in Pekanbaru City with a vision to deliver excellent, quality, and affordable healthcare services supported by competent human resources and accountable management; as nurses are the frontline staff who interact most frequently with patients, their performance is pivotal to service quality and institutional image. This study examines the effects of work–family conflict and job stress on the performance of female inpatient nurses, with work motivation as an intervening variable, at Petala Bumi Regional General Hospital. The population comprised all female inpatient nurses in 2025 (78 individuals), and purposive sampling of married female nurses yielded 56 respondents. Data were analyzed using path analysis with SmartPLS 4. The findings reveal that work–family conflict and job stress have negative and significant effects on nurses’ motivation and performance, while work motivation has a positive and significant effect on performance; moreover, work–family conflict and job stress also exert negative and significant indirect effects on performance through work motivation.